2021
DOI: 10.1080/13625187.2021.1975268
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and continuation with LNG-IUS 12: findings from the real-world kyleena® satisfaction study

Abstract: Purpose: The Kyleena V R Satisfaction Study (KYSS) aimed to assess satisfaction and continuation with levonorgestrel-releasing intrauterine system (LNG-IUS) 12 (Kyleena V R ) in routine clinical practice and to evaluate factors that influence satisfaction. Materials and methods: This prospective, observational, multicentre, single-arm cohort study, with 1-year follow-up, was conducted in Belgium,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…Moreover, most participants reported that they would recommend IUD as post‐abortion contraception to a friend. This confirms similar high satisfaction rates as for other groups of women after interval IUD placement 8,22,23 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, most participants reported that they would recommend IUD as post‐abortion contraception to a friend. This confirms similar high satisfaction rates as for other groups of women after interval IUD placement 8,22,23 …”
Section: Discussionsupporting
confidence: 82%
“…This confirms similar high satisfaction rates as for other groups of women after interval IUD placement. 8,22,23 Whereas long-term data on IUD use after abortion seldom exceeds a 6-months follow-up, Korjamo et al followed patients for 1 year, comparing placement of a H-IUD 52 mg within 3 days of misoprostol administration with delayed placement after medical abortion up to 20 weeks of gestation and found that overall IUD continuation rates were higher in the intervention group than among controls (62.4% vs 39.7%; RR 1.57, 95% CI 1.23-2.02). However, in the gestational age strata of up to 63 days' gestation, the dropout rate among the 108 participants was 40%.…”
Section: Discussionmentioning
confidence: 99%
“…As Germany represented the largest country-speci c KYSS population with 508 of the total 1129 participants, these data re ected the most important conclusions of the multinational KYSS population [33]. These data also further supported the high satisfaction and continuation rates as well as the favorable safety pro le demonstrated with LNG-IUS-19.5mg in prior clinical trials [6,7,32].…”
Section: Discussionsupporting
confidence: 73%
“…The Kyleena™ Satisfaction Study (KYSS) is a multinational, observational study (NCT03182140) providing the first real-world evidence of satisfaction with LNG-IUS-19.5 mg in routine clinical practice [ 31 , 33 ]. Previously published data from the multinational overall cohort from KYSS showed high levels of satisfaction with LNG-IUS-19.5 mg, high continuation rates, and placement that was generally considered easy with little to no pain; however, these results varied notably between country-specific cohorts [ 31 , 33 ]. To further examine this variability, here we reported a subgroup analysis and relevant differences from the German participants in KYSS.…”
Section: Introductionmentioning
confidence: 99%